The influence of online shopping motivation and product browsing toward impulsive buying of fashion products on a social commerce - Wahab, Zakaria; Shihab, Muchsin Saggaf; Hanafi, Agustina; Mavilinda, Hera Febria (JURNAL MANAJEMEN MOTIVASI, 2018)
The purpose of this study is to analyze the direct and indirect influence of onlineshopping motivation and product browsing on impulsive buying, where productbrowsing as a mediation variable between online shopping motivation and impulsivebuying. This study is quantitative. Questionnaires were distributed to women whohave purchased fashion product in social commerce, i.e., Instagram as the targetrespondents. Using a convenience sampling technique, a total sample of 300respondents were obtained. Hypotheses were tested using Structural Equation Model(SEM). The results showed that online shopping motivation on hedonic motivationvariable has a significantly direct effect on product browsing and impulsive buying,while utilitarian motivation variable has significantly direct effect only on productbrowsing. Other than that the product browsing variable has a significantly directeffect on impulsive buying and it's mediating between online shopping motivationand impulsive buying.